Ownership Concentration and Corporate Performance on the Budapest Stock Exchange: Do Too Many Cooks Spoil the Goulash? - John S. Earle; Csaba Kucsera; Almos Telegdy (W.E. Upjohn Institute for Employment Research, 2003)
We examine the impact of ownership concentration on firm performance using panel data for firms listed on the Budapest Stock Exchange, where ownership tends to be highly concentrated and frequently involves multiple blocks. Fixed-effects estimates imply that the l largest block increases return on assets and operating efficiency strongly and monotonically, but the effects of total blockholdings are much smaller and statistically insignificant. Controlling for the size of the largest block, point estimates of the marginal effects of additional blocks are negative. The results suggest that the marginal costs of concentration may outweigh the benefits when the increased concentration involves "too many cooks."
Additional information: A revised version of this paper appears in Corporate Governance, 13(2), 1-11, March 2005.
Keywords: G32; G34; 330; Budapest; stock; exchange; ownership; concentration; Earle